(3eYLe GdOejGWis - (3YHO GdeDef Hf Nda GdOejGWj, CHh eMeO, TQa GdOjf,J (B705 (3g` s
(3ChdgG (B:s
(3jHJOF HeMeO Hf GdMSf s
(3BNQgG (B:s
(3jfJgi HeMeO Hf SdGeI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B34 - (3U(B47s
(3YdjgG SeGYGJ hELGRGJ HYVgG SfI (B681 (3hHYVgG GdBNQ SfI (B705 (3hYdjgG NW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B169 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B197s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B253 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1735s
(3eUOQ GbJfGA GdCUd (B:s
(3GdCRgQ (B((3eUWdM GdMOjK (B( (3eLGejY (B) (326)10660) s
Keywords: (3GdJGQjNs